1998
DOI: 10.1007/bfb0054154
|View full text |Cite
|
Sign up to set email alerts
|

Easy come — Easy go divisible cash

Abstract: Recently, there has been an interest in making electronic cash protocols more practical for electronic commerce by developing e-cash which is divisible (e.g., a coin which can be spent incrementally but total purchases are limited to the monetary value of the coin) [DC94, E094, 0 0 9 2 , Pai93, Oka951. In Crypto'95, T. Okamoto presented the first practical divisible, untraceable, off-line e-cash scheme, which requires only O(logh/) computations for each of the withdrawal, payment and deposit procedures, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(105 citation statements)
references
References 15 publications
0
105
0
Order By: Relevance
“…These technologies include anonymous credential systems [1,2,3], pseudonym systems [4,5,6,7], anonymous e-cash [8,9,10], or direct anonymous attestation [11]. Almost all of these schemes exhibit a common architecture with certificate issuers, users (certificate recipients) and certificate verifiers: Users obtain a signature from an issuing authority on a number of attributes and, at later time, can convince verifiers that they indeed possess a signature on those attributes [12].…”
Section: Introductionmentioning
confidence: 99%
“…These technologies include anonymous credential systems [1,2,3], pseudonym systems [4,5,6,7], anonymous e-cash [8,9,10], or direct anonymous attestation [11]. Almost all of these schemes exhibit a common architecture with certificate issuers, users (certificate recipients) and certificate verifiers: Users obtain a signature from an issuing authority on a number of attributes and, at later time, can convince verifiers that they indeed possess a signature on those attributes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Such kind of proofs are intensively used in several schemes: electronic cash systems [7], group signatures [11], publicly verifiable secret sharing schemes [17,4], and other zero-knowledge protocols (e.g. [13,10]).…”
Section: Introductionmentioning
confidence: 99%
“…Following Chaum's paradigm many schemes were proposed [11,16,7,12,14]. The one due to Brands [11] is known for its efficiency during spending, however, a formal proof of security has never been given for it and it has been recently shown that it cannot be proven secure in the Random Oracle model using currently known techniques [5].…”
Section: Related Workmentioning
confidence: 99%